Resilience in childhood - Fridman Markewitz, Mary (2005)
This article is about resilience, a contemporary word referent to the human being capacity to face adverse conditions and recover from them. However no children can turn resilient by himself. He should have learned, during his first childhood, the affective relationships that let him save in his memory an internal stability process. This is studied from its etymological origins, going through diverse focus used until now considering risky factors, generating conditions of resilience and the different ways of acting from our own point of view.